PENINGKATAN HASIL BELAJAR LUAS TRAPESIUM DAN LAYANG-LAYANG MENGGUNAKAN MODEL PEMBELAJARAN TAI DI SEKOLAH DASAR - NOVITA, NOVA (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
Abstract This research was done due to the fact that teachers dominated the learning process and still used the conventional approach in the learning process. This research aimed at describing the improvement of students’ trapezoids and kites learning outcomes by using the team assited individualization model. The design of the research was class action research using both qualitative and quantitative approaches.The subjects of the research were the teacher and twenty three fifth grade student of SDN 15 Koto Merapak that consisted of 11 boys and 12 girls. The result of the lesson plan analysis in cycle I was 76,56% and in cycle II was 90,62 %. Students’ learning outcome in cycle I was 73,47% and it increased in cycle II to 82,32 % Thus, the team assisted individualization model successfully improved students’ trapezoids and kites leaning outcomes Keywords: Trapezoids and Kites learning Outcomes, the Team Assisted Individualization Model